Jesus Christ superstar - Rice, Tim.; Lloyd Webber, Andrew 1948-.; Edwards, Gale. ([USA] The Really Useful Group, 2000)
The popular rock musical version based on the show's Broadway revival, re-orchestrated and set to modern times.
Lyrics: Tim Rice ; music: Andrew Lloyd Webber ; executive producers: Austin Shaw and Kevin Wallace ; film directors: Nick Morris and Gale Edwards.
Cast : Glenn Carter, Jerome Pradon, Renee Castle and Rick Mayall.
Keywords: Operas; Rock music -- 1971-1980.; Passion music; Popular music